Sex-related differences in arterial spin-labelled perfusion of metabolically active brain structures in neonatal hypoxic–ischaemic encephalopathy. Issue 5 (May 2021) - Zheng, Q.; Freeman, C.W.; Hwang, M.
Abstract : AIM: To investigate the sex-related differences in arterial spin-labelled (ASL) perfusion of metabolically active brain structures in neonatal hypoxic–ischaemic encephalopathy (HIE). MATERIALS AND METHODS: Seventy-three term neonates were identified for a retrospective case–control study following an institutional review board (IRB) approved protocol. The cerebral pulsed arterial spin labelling values were compared by permutation test to identify metabolically active brain structures with significant perfusion changes between 10 male controls and eight female controls, and between 31 HIE males and 24 HIE females. RESULTS: In the perfusion comparison between HIE male and female neonates, significantly lower perfusion was found in the thalamus in males ( p= 0.02). The other brain clusters, including basal ganglia, hippocampus cluster, cingulate gyrus cluster, brainstem cluster, sensorimotor cortex cluster, and cerebellum and peduncle cluster, demonstrated no significant differences between HIE males and females. In the perfusion comparison between male and female controls, there were no significant perfusion changes in those brain clusters. CONCLUSION: Brain perfusion in neonatal HIE differs between males and females in the thalamus, a metabolically active region within neonates, with males demonstrating lower perfusion. This difference in perfusion may reflect sex-related disparities in response to and recovery from hypoxic–ischaemic events. Highlights: Significantly lower perfusion was found in the thalamus in males than females. There were no significant perfusion changes between male and female controls. This may reflect sex-related disparities in hypoxic-ischemic events.